"Strange Fruit": Teaching the Present and Past of Racial Violence in the Rural South. Issue 2 (3rd April 2021) - Gibbs, Brian
ABSTRACT: Drawing from data from a multicase study, I examined how teachers teach current racial violence and for racial justice in rural school spaces in the U.S. South. Using abolitionist teaching and trauma-informed pedagogy as theoretical lenses, I argue that racial violence and racial justice can be taught well even in schools in complex political, social, and ideological communities. Teachers need to assume racial trauma in all students, connect the past and present of racial violence and resistance, frame teaching for the space in which the teaching is done, and finally, affirm the experiences of students of color, recognizing both the violence and the resistance.